Pre-reproductive maternal enrichment influences rat maternal care and offspring developmental trajectories: behavioral performances and neuroplasticity correlates - Cutuli, Debora (Front Behav Neurosci, 2015)
Environmental enrichment (EE) is a widely used paradigm for investigating the influence of complex stimulations on brain and behavior. Here we examined whether pre-reproductive exposure to EE of female rats may influence their maternal care and offspring cognitive performances. To this aim, from weaning to breeding age enriched females (EF) were reared in enriched environments. Females reared in standard conditions were used as controls. At 2.5 months of age all females were mated and reared in standard conditions with their offspring. Maternal care behaviors and nesting activity were assessed in lactating dams. Their male pups were also behaviorally evaluated at different post-natal days (pnd). Brain BDNF, reelin and adult hippocampal neurogenesis levels were measured as biochemical correlates of neuroplasticity. EF showed more complex maternal care than controls due to their higher levels of licking, crouching and nest building activities. Moreover, their offspring showed higher discriminative (maternal odor preference T-maze, pnd 10) and spatial (Morris Water Maze, pnd 45; Open Field with objects, pnd 55) performances, with no differences in social abilities (Sociability test, pnd 35), in comparison to controls. BDNF levels were increased in EF frontal cortex at pups' weaning and in their offspring hippocampus at pnd 21 and 55. No differences in offspring reelin and adult hippocampal neurogenesis levels were found. In conclusion, our study indicates that pre-reproductive maternal enrichment positively influences female rats' maternal care and cognitive development of their offspring, demonstrating thus a transgenerational transmission of EE benefits linked to enhanced BDNF-induced neuroplasticity.